Labor force and economic growth based on demographic pressures, happiness, and human development: Empirical from Romania - Wijaya, Adi; Kasuma, Jati; Tasen?e, T?nase; Caisar Darma, Dio (Journal of Eastern European and Central Asian Research (JEECAR), 2021)
This article examines the effects of DP, HI, and HDI on LF and EG in Romania for the period 2013-2019. By using path analysis, we need to divide into two models (direct effect and indirect effect. With a time series database, calculations can be presented through the data obtained in the annual report. The article documents six important findings, including the variables DP, HI, and HDI supports EG significantly. Moreover, HDI and LF also play an important role in EG significantly, but HDI is the single most striking variable from the hypothesis test, it is proven that the effect also has a significant effect on EG through LF. This evidence offers insights to stakeholders that there needs to be an emphasis from DP and HI so that they can play a real role for the success of the population's welfare.